The false cause : fraud, fabrication, and White supremacy in Confederate memory - Domby, Adam H., 1983- (The University of Virginia Press, 2020)
"This book examines the foundational role of deliberate misrepresentation in various elements of white supremist Lost Cause mythology, from Confederate soldiers' military prowess, loyalty, motivation, and unity, to mythical black Confederates, to the evolution of Lost Cause myths to support present-day white supremacy. It adds to the understanding of the memory and reality of the American Civil War as American society debates historical monuments and sees the mainstream rise of emboldened white supremacist political groups"--